1965
DOI: 10.2307/1970644
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-fonctions et Hauteurs sur les Varietes Abeliennes

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
4

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(64 citation statements)
references
References 4 publications
0
60
0
4
Order By: Relevance
“…This follows immediately from Theorem 2 in [34] once we have shown that for −1 − a ≤ σ ≤ 1 + b we have (29) |f λ,χ (σ + it, g)| ≤ c 1 e…”
Section: Lemma 85mentioning
confidence: 71%
See 1 more Smart Citation
“…This follows immediately from Theorem 2 in [34] once we have shown that for −1 − a ≤ σ ≤ 1 + b we have (29) |f λ,χ (σ + it, g)| ≤ c 1 e…”
Section: Lemma 85mentioning
confidence: 71%
“…This is less trivial than the example given above because one has to determine a fundamental domain modulo the action of the units (the proofs appeared in [39]). In 1965, Neron [29] gave asymptotics for the number of rational points of bounded height on abelian varieties. The classical circle method, now a whole field in itself, proves asymptotics on complete intersections of small degree.…”
Section: Introductionmentioning
confidence: 99%
“…A Néron-Tate height function [18] is the unique representative of the class of height functions attached to a line bundle that is in reality a function of degree at most two, namely, a quadratic form plus a linear functional on A(Q). The quadratic part of a Néron-Tate height function associated with an ample line bundle N on A gives a non-degenerate non-negative quadratic form on the real iv vector space R ⊗ A(Q).…”
Section: ∈ Pic V We Have H(l ⊗ M P ) = H(l P ) + H(m P ) + O(1mentioning
confidence: 99%
“…This is applied to the distribution of integral points on abelian varieties in Section 5.4. where h (w, z) is a hermitian quadratic form on C^ and K (k) is real valued. Then for all zeC^ one has (see [33]) <D, (^(z))-(9)>,= -log |9(z)|+7r/2^(z, z). The subscript v added to one of the above symbols denotes that it is relative to the valuation v, if more than one valuation is being considered.…”
Section: Local Neron Heights and Integral Pointsmentioning
confidence: 99%